2017
DOI: 10.1515/hc-2017-0064
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and pharmacological research on the plants from genus Ajuga

Abstract: The genus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 104 publications
0
15
0
Order By: Relevance
“…Interestingly, we observed no protective effect of the prior exposure of individual sawflies to clerodanoids, neither in the presence, nor absence of the fungus. This is an unexpected result considering that some clerodanoids show antifungal activity (reviewed by Li et al, 2016 ; Qing et al, 2017 ). The lack of a protective effect in this interaction suggests that the in vitro antimicrobial activity reported for some clerodanoids does not necessarily translate into a better protection against a potential pathogen in vivo .…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, we observed no protective effect of the prior exposure of individual sawflies to clerodanoids, neither in the presence, nor absence of the fungus. This is an unexpected result considering that some clerodanoids show antifungal activity (reviewed by Li et al, 2016 ; Qing et al, 2017 ). The lack of a protective effect in this interaction suggests that the in vitro antimicrobial activity reported for some clerodanoids does not necessarily translate into a better protection against a potential pathogen in vivo .…”
Section: Discussionmentioning
confidence: 90%
“…Much phytochemical research has assessed the separation of Ajuga ingredients. These studies have led to the isolation of several secondary metabolites, including neo-clerodane_diterpenes and diterpenoids, phytoecdysteroid components, flavonoid derivatives, iridoids, sesquiterpenoid compounds, withanolides, phenylethanoid glycoside derivatives, sterols, anthocyanins, and O-coumaric acid compounds (3,8,12,13,15,23,29,34,39,40,(45)(46)(47)(48)(49)(50)(51). Isolated compounds from different Ajuga species growing in Iran are shown in Table 2.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…A. decumbens is highly rich in diterpenoids as other Ajuga species, diterpenoids from A. decumbens are of two groups that are neoclerodane and abietane [11,[17][18]. Eight diterpenoids were isolated from ethanol extract of A. decumbens, including Ajugacumbins A (1), Ajugacumbins B (2), Ajugacumbins C (3), Ajugacumbins D (4), Ajugamarins A2 (5), Ajugamarins G1(6), Ajugamarins H1(7) and Ajugamarins F4 (8) [19][20].…”
Section: Diterpenoidsmentioning
confidence: 99%
“…The genus Ajuga, belongs to the family of Labiatae, commonly known as "Bugleweed or Ground pine" [1] which distributed mainly in the temperate regions Europe, Asia and Africa [2] where most its species can be found, but only two of Ajuga species are available in southeastern Australia [3][4]. Pharmacological studies revealed that Ajuga possessed, have been used as anti-inflammatory agents, anticancer, astringent, anthelmintic, hypoglycemic, febrifuge diuretic, insecticidal properties and antifungal [5][6][7][8][9][10][11]. Ajuga decumbens is used as a folk medicine for the treatment of all kinds of ailment in ancient, most especially in China and Japan [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%